DIGITALIZATION OF PUBLIC CATERING IN UZBEKISTAN - Pardayeva Ozoda; Raxmatullayev Shoxrux (Journals Park Publishing, 2023)
Currently, consumers do not have the opportunity to know the roadmap of agricultural products that they consume in catering places. Visitors to public catering places have little information about how dishes are prepared, where agricultural products are brought from, how the logistics of products are carried out and the conditions for storing products. In the age of developing technologies, there is no problem of digitalization of any sphere. In order to ensure the sustainability and competitiveness of restaurants and cafes in today's economic conditions, especially in the case of new emerging catering establishments and attracting visitors, it is almost impossible to imagine without a digital transformation process, whether it is a marketing side or any other side of this activity. Despite the ever-increasing complexity of food systems, digital technologies allow us to collect and analyze a wealth of data from a virtually unlimited number of sources at all stages of the food chain.
Keywords: Digitalization, roadmap, logistics, agricultural products, marketing, potential client